British travelers’ impressions of the Russians during the reign of Alexander II - Iwona Sakowicz (Studia Litterarum)
This article examines the image of Russia and its people in the travelogues of British travelers during the rule of Alexander II (1855–1881). In reality, hardly anybody from Britain visited the country of the tsars, and very few could speak its language. The upper classes, mostly nobility, surprised English visitors with their Western European looks, good manners, and elegance. However, generalizations about Russians as a nation were based on the observations of lower classes, mostly coachmen. Russians in the opinion of the travelers were faithless, servile, and lazy. Slavonic passivity made them perfectly fit for the absolutist rule. Russia was perceived as a semi-barbaric and despotic country. Over the period of 25 years, there were no substantial changes in the travelers’ descriptions of the country.